FILANTROPI DAN PENDIDIKAN ISLAM DI INDONESIA - Hilman Latief (Jurnal Pendidikan Islam, 2013)
This article tries to discuss the possibility that Islam philantropy can contribute to the development of education in Indonesia. In the context of Islamic education in Indonesia, the tradition of philantropy can be found in alms and benefaction for educational institution. Therefore, Dompet Duafa established Lembaga Pengembangan Insan (Human Resource Development Institution), Rumah Zakat Indonesia designed Sekolah Juara (School for the Champions) and breeding program of reciting Quran had BASIQ program (Scholarship for students who learn Quran), EKSPOR (Productive Economy of Pesantren) and Daqu School (Darul Quran School). These Islamic philantropy institutions had put no concern on Islamic University as main partner yet. Whereas their involvement to support research in university level, specifically regarding Islamic studies, is significantly needed since it provides balance to the development of Islamic studies in the West which is also funded by Muslim philantropists such Bin Laden family and Abassi family and the Saudi Royal family.